Hope as a Primitive Mental State. (23rd January 2015) - Segal, Gabriel; Textor, Mark
Abstract We criticize attempts to define hope in terms of other psychological states and argue that hope is a primitive mental state whose nature can be illuminated by specifying key aspects of its functional profile.1